2019
DOI: 10.1186/s12864-019-5989-2
|View full text |Cite
|
Sign up to set email alerts
|

Cut-C: cleavage under tethered nuclease for conformational capture

Abstract: Background Deciphering the 3D structure of the genome is essential for elucidating the regulatory mechanisms of gene expression in detail. Existing methods, such as chromosome conformation capture (3C) and Hi-C have enabled the identification of novel aspects of chromatin structure. Further identification of protein-centric chromatin conformation is enabled by coupling the Hi-C procedure with a conventional chromatin immunoprecipitation assay. However, these methods are time-consuming and require … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Skene et al have showed that their new in situ methods, such as cleavage under targets and release using nuclease (CUT&RUN) and cleavage under targets and tagmentation (CUT&Tag), will be viewed as a cost-effective and versatile alternative to ChIP because of low backgrounds, which requiring only ∼1/10th the sequencing depth as ChIP (Skene and Henikoff, 2017;Skene et al, 2018;Kaya-Okur et al, 2019;Meers et al, 2019). Based on these methods, Shimbo et al (2019) have developed cleavage under tethered nuclease for conformational capture (Cut-C) technology to identify chromatin interactions mediated by a protein of interest along with the genome-wide distribution of the target proteins. Thus, using these latest technologies, we may be clearly captured the accuracy of chromatin loops mediated by ZNF143 in a genome-wide scale.…”
Section: Conclusion and Prospectsmentioning
confidence: 99%
“…Skene et al have showed that their new in situ methods, such as cleavage under targets and release using nuclease (CUT&RUN) and cleavage under targets and tagmentation (CUT&Tag), will be viewed as a cost-effective and versatile alternative to ChIP because of low backgrounds, which requiring only ∼1/10th the sequencing depth as ChIP (Skene and Henikoff, 2017;Skene et al, 2018;Kaya-Okur et al, 2019;Meers et al, 2019). Based on these methods, Shimbo et al (2019) have developed cleavage under tethered nuclease for conformational capture (Cut-C) technology to identify chromatin interactions mediated by a protein of interest along with the genome-wide distribution of the target proteins. Thus, using these latest technologies, we may be clearly captured the accuracy of chromatin loops mediated by ZNF143 in a genome-wide scale.…”
Section: Conclusion and Prospectsmentioning
confidence: 99%
“…This article is protected by copyright. All rights reserved combines antibody-mediated cleavage by tethered nuclease with chromosome conformation capture (Shimbo et al, 2019); Capture Hi-C: a method that combines Hi-C with the hybridization-based capture of targeted genomic regions (Mifsud et al, 2015); In situ Hi-C: a method in which DNA-DNA proximity ligation is performed in intact nuclei (Rao et al, 2014); Micro-C: a method in which chromatin is fragmented into mononucleosomes using micrococcal nuclease (Hsieh et al, 2015); Dnase Hi-C: a method in which chromatin is fragmented by DNase I (Ma et al, 2015); DLO Hi-C: Digestion-ligation-only Hi-C technology that requires two rounds of digestion and ligation, without the need for biotin labeling and pulldown (Lin et al, 2018); BAT Hi-C: Bridge linker-Alul-Tn5 Hi-C method that combines Alul fragmentation with biotinylated linker-mediated proximity ligation ; BL-Hi-C: Bridge Linker-Hi-C that requires restriction enzyme targeting and two-step proximity ligation (Liang et al, 2017); Trac-looping: transposase-mediated analysis of chromatin looping (Lai et al, 2018); Methyl-HiC: a method that combines Hi-C and DNA methylation detection technology (Li et al, 2019b); OCEAN-C: open chromatin enrichment and network Hi-C ; Single cell Hi-C: a method to perform Hi-C in an individual nucleus (Nagano et al, 2013). Asterisks show the methods that have been applied to plants.…”
Section: Accepted Articlementioning
confidence: 99%
“…The recently developed techniques like Trac-looping (transposase-mediated analysis of chromatin looping) for simultaneous detection of multiscale genome-wide chromatin interactions among regulatory elements and chromatin accessibility ( Lai et al, 2018 ), and OCEAN Hi-C (open chromatin enrichment and network Hi-C) for antibody-independent mapping of global open chromatin interactions ( Li T. et al, 2018 ) were used to decipher the chromatin architecture. More recently, Cut-C combined antibody-mediated cleavage by tethered nuclease with chromosome conformation capture to identify chromatin interactions mediated by a protein of interest ( Shimbo et al, 2019 ). Cut-C identifies protein-centric chromatin conformations along with the genome-wide distribution of target proteins using a simple procedure.…”
Section: 3d Genome Mapping Techniquesmentioning
confidence: 99%
“…Cut-C identifies protein-centric chromatin conformations along with the genome-wide distribution of target proteins using a simple procedure. Applying Cut-C to a histone modification (H3K4me3) enriched at active gene promoters, Shimbo et al (2019) could successfully identify the chromatin loops mediated by H3K4me3 along with the genome-wide distribution of H3K4me3. Further, methyl Hi-C (DNA methylation detection combined with Hi-C) for simultaneous capture of chromosome conformation and DNA methylome was used to delineate the DNA methylation profile and chromatin architecture of a cell ( Li G. et al, 2019 ).…”
Section: 3d Genome Mapping Techniquesmentioning
confidence: 99%
See 1 more Smart Citation